Estimanon of Potential Germinability of Teak (Tectona grandis Linn. f) Fruits from Twenty Three Indian Sources by Cutting Test - Gupta, B. N.; Kumar, Adarsh (Indian Forester, 1976)
Mass collected teak fruits from twenty three sources received from the forest departments of fine states of India were studied for relative seededness and emptinesea. The study revealed that the emptiness varies from one source to another, and also that the number of seeds in teak fruits range from 0 to 4. It is also observed that frequency of distribution of one seeded fruits is the highest, followed by the fruits with two seeds. Three seeded fruits are still less frequent and four seeded ones very rare.